2020
DOI: 10.3390/pharmacy8040181
|View full text |Cite
|
Sign up to set email alerts
|

Patient Screenings for Preconception Health Interventions at a Community Pharmacy

Abstract: Preconception health refers to health before pregnancy and involves addressing risk factors that can negatively impact either a patient or future pregnancy. Pharmacists can play an essential role in screening for and managing patients’ risk factors to optimize pregnancy outcomes. The primary objective of this study is to determine whether preconception health screenings in community pharmacy settings identify opportunities for preconception health services, particularly pharmacy-based interventions. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Of the 23 included articles ( Table 2 ), three solely involved health professionals [ [20] , [21] , [22] ]. A further five elicited the attitudes and beliefs of HCPs and women within the same study [ [23] , [24] , [25] , [26] , [27] ], and 15 solely involved women [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 23 included articles ( Table 2 ), three solely involved health professionals [ [20] , [21] , [22] ]. A further five elicited the attitudes and beliefs of HCPs and women within the same study [ [23] , [24] , [25] , [26] , [27] ], and 15 solely involved women [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 1478 articles, and an additional two articles were identified through searching of reference lists. Following screening of titles and abstracts, ten articles were eligible for full text screening, of which four were included [ 20 , 21 , 22 , 23 ] and six excluded [ 16 , 17 , 24 , 25 , 26 , 27 ]. Reasons for exclusion included incorrect intervention setting, inappropriate study design or a target population that did not include pregnant women or those planning pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review in 2019 demonstrated uptake and acceptance of contraceptive interventions provided by community pharmacists and highlighted the opportunities to expand and integrate preconception care services including counselling on folic acid use [ 38 ]. Furthermore, a US study identified numerous opportunities in community pharmacy settings for pharmacists to provide preconception care services including screening for folic acid supplementation [ 26 ]. Together with the findings of this review, public health initiatives should consider community-based pharmacists to deliver interventions to improve folic acid knowledge and usage in preconception women.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides the first insights of knowledge, comfort, and motivation among pharmacists regarding the provision of pharmacologic interventions for healthy pregnancies. After (13) Pharmacists can identify eligible patients by screening for medications related to pregnancy or postpartum management, as well as addressing medication safety concerns during pregnancy or breastfeeding. Pharmacists can also provide chronic disease state management to reduce risk of preeclampsia in current or future pregnancies.…”
Section: Discussionmentioning
confidence: 99%